Optimal Design of DC to DC Boost Converter with Closed Loop Control PID Mechanism for High Voltage Photovoltaic Application - R. Arulmurugan; N. Suthanthira Vanitha (Institute of Advanced Engineering and Science, 2012)
This paper proposes a new dc to dc boost converter using closed loop control proportional Integral and Derivative mechanism for photovoltaic (PV) standalone high voltage applications. The boost converter is composed of MOSFETs which are driven by closed loop PWM control. Many advantages including high efficiency, minimum number of switch, high voltage and power, low cost. This converter is attractive for high voltage and high power applications. The analysis and design considerations of the converter are presented. A prototype was implemented for an application requiring a 410W output power, input voltage range from 17.1-V, and a 317-V output voltage. The proposed system efficiency is about 90%.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.2126